Inclusive Education: In Concepts, Policies, and Implementation - Esty Zyadatul Khasanah (The Center for Disability Studies and Services Brawijaya University, 2018)
This research purposed to examine the conformity of concepts and policy of inclusive education, to its implementation in the field in realizing the quality of education. Inclusive education is an effort to provide access to education for every citizen, including those with special needs. Inclusive education must be well managed, so that policy and their implementation are in accordance with the underlying concepts. The method used in this research is descriptive analysis with literature review approach and empirical. As well as conducting case studies in the field by observing inclusive school organizers to view data empirically. The results of the study are seen from inclusive education issues at the school level, including: understanding and implementation, school policy, learning process, teacher condition, and support system.